The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1159/000139062
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence for Prejunctional GABA-B Inhibition of Cholinergic and Peptidergic Bronchoconstriction in Guinea Pigs: Studies with New Agonists and Antagonists

Abstract: We examined the effect of the potent and selective GABA-B agonists, baclofen, 3-aminopropylphosphinic acid (3-APPi) and 3-aminopropyl (methyl) phosphinic acid (SKF 97541), and the GABA-B antagonists, 3-aminopropyl (diethoxymethyl) phosphinic acid (CGP 35348), 2-hydroxysaclofen and 3-aminopropylphosphonic acid (3-APPA) on cholinergic and peptidergic contractile responses in the airways of guinea pigs. Electrical field stimulation of the isolated guinea pig trachea produced cholinergic contractions that were ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 16 publications
3
8
0
Order By: Relevance
“…In contrast with the findings of Tamaoki et al, 8 but in agreement with the findings of others in tissues such as trachea, 12,41 lung, 9 ileum, 42,43 distal colon 44 muscle 45 from rats, 43,45 guinea-pigs 8,9,12,41,42,45,46 and rabbits, 44 the effect of GABA appeared to be mediated by the GABAB receptor because it was mimicked by baclofen and antagonized by phaclofen. The GABAA receptor does not appear to be involved in this effect, because it was neither mimicked by 3-APS nor modified by bicuculline.…”
Section: Discussionsupporting
confidence: 79%
“…In contrast with the findings of Tamaoki et al, 8 but in agreement with the findings of others in tissues such as trachea, 12,41 lung, 9 ileum, 42,43 distal colon 44 muscle 45 from rats, 43,45 guinea-pigs 8,9,12,41,42,45,46 and rabbits, 44 the effect of GABA appeared to be mediated by the GABAB receptor because it was mimicked by baclofen and antagonized by phaclofen. The GABAA receptor does not appear to be involved in this effect, because it was neither mimicked by 3-APS nor modified by bicuculline.…”
Section: Discussionsupporting
confidence: 79%
“…Conversely, GABA receptors have never been described in airway smooth muscle itself. It has been known for some time that GABA B -specific agents decrease electrically fieldstimulated airway constriction by modulating acetylcholine release from parasympathetic nerves (13,14,33,53,55). This is mediated by a presynaptic inhibition of acetylcholine release by GABA B receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Their studies led cumulative investigations on the response to GABA and GABA agonists in a series of peripheral organs and a number of suggestive studies on the modulator role for GABA in the heart (5), the lung (6), and in the regulation of the peristaltic reflex (7) and adrenal catecholamine secretion (8). Since 1995, we have shown that inhibitory mechanisms in rat salivary gland were regulated by a GABA A receptor (GABA A -R)-chloride ion channel complex: it was demonstrated that GABA and its biosynthetic and metabolic enzyme existed in rat salivary gland (9,10); and GABA and benzodiazepines accelerated 36 Cl − influx (11) and inhibited amylase release (12) in rat parotid gland acinar cells in vitro.…”
Section: Introductionmentioning
confidence: 99%